Electropulsing-induced plastic deformation in an interstitial free steel. Issue 2 (22nd January 2022) - Raut, P.; Fuloria, D.; Baka, S.; Chatterjee, S.; Ghosh, C.; Venkatramani, N.; Samajdar, I.
Abstract : Direct observations on electropulsing (EP)-induced microstructural evolution, in interstitial free (IF) steel with different prior rolling reductions, brought out clear evidence of plastic deformation, changes in mesostructures and local mechanical properties. Although plastic strains and strain modes differed widely among the surface grains, these appeared orientation-dependent. In particular, the microstructural evolution was more pronounced when prior cold work was present and also along the transverse direction to the introduced EP. Finite element simulations showed a significant difference in locational and directional dependence of simulated magnetic flux density and stored magnetic energy. It appears that magnetic Lorentz force, providing torque to dislocation dipoles, acted as the mechanistic origin behind the microstructural changes.